Identification of Spectral Modifications Occurring during Reprogramming of Somatic Cells - Sandt, Christophe (Public Library of Science, 2012)
Recent technological advances in cell reprogramming by generation of induced pluripotent stem cells (iPSC) offer major perspectives in disease modelling and future hopes for providing novel stem cells sources in regenerative medicine. However, research on iPSC still requires refining the criteria of the pluripotency stage of these cells and exploration of their equivalent functionality to human embryonic stem cells (ESC). We report here on the use of infrared microspectroscopy to follow the spectral modification of somatic cells during the reprogramming process. We show that induced pluripotent stem cells (iPSC) adopt a chemical composition leading to a spectral signature indistinguishable from that of embryonic stem cells (ESC) and entirely different from that of the original somatic cells. Similarly, this technique allows a distinction to be made between partially and fully reprogrammed cells. We conclude that infrared microspectroscopy signature is a novel methodology to evaluate induced pluripotency and can be added to the tests currently used for this purpose.